Bóg Arystotelesa i Bóg Jezusa Chrystusa a Bóg człowieka dzisiaj - Anna Gładkowska (Wrocławski Przegląd Teologiczny)
In contemporary culture is emerging a problem, which interest the public opinion – it is about faith in God, which is a challenge for the world. Existing difficulties, never-ending doubts, as well as objections to the Christian conception of life are the causes of departing the XXI century man from God. Requirements of Christianity are seen as too arduous and outdated, and as a result, many people resort to his vision of an easier life. The apparent respect commands man, who managed to convince, that following Christ deprives liberty and opposed to human happiness. The author of this study presents a passage, that has come to the people: from the perception of God as an impersonal force, through a personal God revealed in Jesus of Nazareth, to the god, who is identify with power, success, prestige and money – he is the god of “today”.